2003
DOI: 10.1089/152702903769192250
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Hypoxia Improves Endurance Performance and Submaximal Exercise Efficiency

Abstract: The purpose of the present study was to elucidate the influence of intermittent hypobaric hypoxia at rest on endurance performance and cardiorespiratory and hematological adaptations in trained endurance athletes. Twelve trained male endurance runners were assigned to either a hypoxic group (n = 6) or a control group (n = 6). The subjects in the hypoxic group were exposed to a simulated altitude of 4500 m for 90 min, three times a week for 3 weeks. The measurements of 3000 m running time, running time to exhau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
85
2
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(103 citation statements)
references
References 42 publications
11
85
2
5
Order By: Relevance
“…Recently, Lundby and colleagues (2005) concluded that 120 min of hypobaric hypoxia was not great enough to cause a significant increase in EPO; yet their data produced a mean increase of 31.6%. It is at least plausible that the lack of a statistical change in EPO in the Lundby et al (2005) study and other work (Katayama et al, 2003) may have been due to error of measurement (TEM). However, this is at best speculative, as the authors did not publish these data.…”
Section: Acute Normobaric Hypoxia Stimulates Erythropoietin Releasementioning
confidence: 87%
See 2 more Smart Citations
“…Recently, Lundby and colleagues (2005) concluded that 120 min of hypobaric hypoxia was not great enough to cause a significant increase in EPO; yet their data produced a mean increase of 31.6%. It is at least plausible that the lack of a statistical change in EPO in the Lundby et al (2005) study and other work (Katayama et al, 2003) may have been due to error of measurement (TEM). However, this is at best speculative, as the authors did not publish these data.…”
Section: Acute Normobaric Hypoxia Stimulates Erythropoietin Releasementioning
confidence: 87%
“…Hypoxic-induced elevations in EPO and so possible increased erythropoiesis has clear tangible benefits for both athletic (Stray-Gundersen et al, 2001) and clinical (Silverberg et al, 2004;Corwin, 2004) populations. However, other investigations have failed to conclude the effectiveness of acute on intermittent hypoxia (Vallier et al, 1996;Katayama et al, 2003;Julian et al, 2004). For a review, see Wilber (2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, for moderately trained individuals used within the study, there b b b ' merely reflect a reduction in perceived exertion and improved thermal comfort under heat stress. Previous studies investigating various interventional strategies on 3 km performance, include intermittent hypoxic (Stray-Gundersen, et al, 2001;Katayama, et al, 2003Katayama, et al, , 2004Rodriguez et al, 2007), plyometric (Spurrs et al, 2003;Pellegrino et al, 2015) and intense training periods (Smith et al, 1999;Coutts, et al, 2007;Esfarjani, et al, 2007), reporting a vast range in improvements from 0.8 to 7.3%. However, the le ' aerobic fitness level, running experience, length and method of intervention vary considerably and so comparisons to this study must be interpreted lightly.…”
Section: 4mentioning
confidence: 99%
“…Lo mismo sucede en el estudio de Hinckson, Hopkins, Downey y Smith (2006) en el que se aplicó un programa de 14 sesiones de 90 minutos de duración entre el 80-92% de la SpO2 en remeros. También existen otras investigaciones previas (Calbet et al, 2003;Consolazio, Nelson, Matoush & Hansen, 1996;Wolfel, Groves & Brooks, 1991;Tadibi, Dehnert, Menold & Bartsch, 2007) que utilizan la exposición a hipoxia intermitente como estímulo, donde el umbral anaeróbico no se modificó o incluso descendió trasun programa de altitud simulada (Katayama, Matsuo, Ishida, Mori & Miyamura, 2003;Lundby, Nielsen & Dela, 2005). Los resultados de nuestra investigación son compartidos por Bonetti et al (2009) que observaron un incremento del 6.5% en la potencia generada en el umbral anaeróbico de 18 triatletas y ciclistas después de 15 sesiones de 60 minutos de duración a una SpO2 del 76-90% o por Friedmann et al (2005) que observaron un incremento del 3 % en la velocidad del umbral anaeróbico tras un programa de IHE de 4 horas diarias al 15 % del FiO2 en 16 nadadores.…”
Section: Discussionunclassified